Ответы и объяснения

  • 6575
  • почетный грамотей
2013-04-01T03:42:33+04:00

f(x) = x^3-6x^2+5
f'(x) = 3x^2-12x
3x^2-12x=0
x^2-4x=0
x(x-4)=0
x=0; x=4
  +          -           +
----(0)-----(4)-----> x

Производная отрицательна на [0;4], значит, функция убывает на [0;4] 

2013-04-01T05:57:20+04:00

производная: 3x²-12x

к нулю: 3x²-12x=0  x²-4x=0 x*(x-4)=0 x=0 x=4

           +                                 -                       +

-----------------0---------------------4--------------------->

Ответ: (0;4)

 

Выбираем лучшее решение!